2014
DOI: 10.1016/j.preteyeres.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Müller glia: Stem cells for generation and regeneration of retinal neurons in teleost fish

Abstract: Adult zebrafish generate new neurons in the brain and retina throughout life. Growth-related neurogenesis allows a vigorous regenerative response to damage, and fish can regenerate retinal neurons, including photoreceptors, and restore functional vision following photic, chemical, or mechanical destruction of the retina. Müller glial cells in fish function as radial-glial-like neural stem cells. During adult growth, Müller glial nuclei undergo sporadic, asymmetric, self-renewing mitotic divisions in the inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
303
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(340 citation statements)
references
References 358 publications
(676 reference statements)
18
303
0
4
Order By: Relevance
“…The response to damage in Ascl1-expressing Müller glia has some features in common with the response of these cells in the fish in that they down-regulate Rlbp1 and other glial genes, while increasing their expression of progenitor genes (33)(34)(35). However, in the zebrafish, the initial mitotic division of the Müller glia produces progenitor cells that continues to divide to generate new neurons (2,34), whereas in Ascl1-expressing mouse Müller glia, the amount of mitotic division is much lower, even with Ascl1 expression. Thus, additional factors will be required to produce a full regenerative response in adult mice more like that in fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response to damage in Ascl1-expressing Müller glia has some features in common with the response of these cells in the fish in that they down-regulate Rlbp1 and other glial genes, while increasing their expression of progenitor genes (33)(34)(35). However, in the zebrafish, the initial mitotic division of the Müller glia produces progenitor cells that continues to divide to generate new neurons (2,34), whereas in Ascl1-expressing mouse Müller glia, the amount of mitotic division is much lower, even with Ascl1 expression. Thus, additional factors will be required to produce a full regenerative response in adult mice more like that in fish.…”
Section: Discussionmentioning
confidence: 99%
“…reprogramming | glia | regeneration | neurogenesis | eye T he retina of the teleost fish has a remarkable potential to regenerate new neurons after various types of injury (1,2). This regenerative potential is much more limited in birds, where neurotoxic damage leads to regeneration of only a subset of inner retinal neurons.…”
mentioning
confidence: 99%
“…Microglia of the human CNS also exhibit this phenomenon, although possibly exhibiting fewer differences between polarization states (27). Importantly, acutely activated microglia are known to express neuroprotective and regenerative factors, e.g., TGFβ, IGF1, IL-10, LIF, and MANF (74,78), some of which have been shown to stimulate MG proliferation (5,6). Combined, these observations suggest that after an initial reactive response to neuronal cell death microglia may adopt an antiinflammatory phenotype to stimulate stem/ progenitor cell proliferation.…”
Section: Microglia Exhibit Several Hallmarks Of Phagocyte Activation Inmentioning
confidence: 99%
“…S4). However, by 7 dpl, when regenerated photoreceptors are exiting the cell cycle and differentiating, 29,60 pax6a is downregulated in all photoreceptors while neurod and nr2e3 are downregulated in newly postmitotic cones but continue to be expressed in rods (Supplementary Fig. S4).…”
Section: Time Course Of Neurod Expression In the Adult Regenerating Rmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] Recent studies in zebrafish have identified mechanisms that govern the Müller glia response to retinal injury, [34][35][36][37] but information is lacking around the pathways that govern photoreceptor regeneration from Müller glia-derived progenitor cells. The mechanisms that govern retinal regeneration are expected to largely recapitulate embryonic development, 28,29,38 though few molecules have been functionally studied during both events. NeuroD function has not been studied in the adult zebrafish retina, but following photoreceptor ablation neurod is expressed in Müller glia-derived mitotic progenitors, 39 suggesting that NeuroD has a role in photoreceptor regeneration.…”
mentioning
confidence: 99%